Endoscopic versus percutaneous biliary drainage for resectable pancreatic head cancer with hyperbilirubinemia and impact on pancreaticoduodenectomy: A randomized controlled study. (September 2021) - El-Haddad, Hany M.; Sabry, Ahmed A.; Shehata, Gihan M.
Abstract: Background: We hypothesized that percutaneous biliary drainage provides more short-term advantages over endoscopic stenting before pancreaticoduodenectomy. Methods: Between January 2019 and December 2010, a prospective cohort study was conducted. Sixty patients with potentially resectable pancreatic head cancers and high bilirubin levels were stratified into two equal groups according to the method of biliary drainage: endoscopic stenting or percutaneous drainage. The primary outcome measures were operative difficulties and early postoperative morbidity, the secondary outcome was post-drainage complications. Results: Both groups were comparable in age; gender; presenting symptoms, type of malignancy, post-drainage complications, and time intervals between drainage and surgery. Key preoperative significant differences were technically higher but clinical success rates was better in the PTD cohort. ERCP patients had significantly more difficult dissections, more blood loss, longer resection time, more postoperative bile leak, and longer hospital stay. Conclusion: From the operative perspective, patients who underwent PTD in the preoperative setting had fewer morbidities and shorter hospital stay. Large scale studies are required to support the validity of these findings in surgical practice. Highlights: A prospective comparison between preoperative endoscopic stenting and percutaneous drainage before pancreaticoduodenectomy. Pancreatioduodenectomy should be performed once the general condition of the patient allows. The percutaneous approach offered more operative advantages. The post-operative course had less complications in patients prepared by the percutaneous transhepatic drainage method.